The approach to coaching student teams in competitive sports, both amateur and professional, in the realm of sports (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretically, to create and substantiate a plan for training student teams in competitive sports, both at the amateur and professional level.